Exploring the challenges and efforts implemented to improve the academic performance and success of nursing students at a university in the Western Cape - Katlego Dumisani Trevor Mthimunye; Felicity Megan Daniels (Elsevier, 2020)
Satisfactory academic performance and success of undergraduate nursing students is a fundamental goal for schools of nursing worldwide. However, many students are confronted with various challenges that may hinder this endeavour. The study adopted a qualitative approach to explore and describe the challenges experienced by undergraduate nursing students at the identified school of nursing, regarding academic performance and success and the efforts implemented to overcome these challenges. The population (N = 1131) included all undergraduate nursing students at the identified university. The sample (n = 50) was selected through stratified random sampling. Six semi-structured focus group discussions were conducted. Data were analysed by means of thematic analysis. The findings of this study revealed that nursing students experience challenges related to: (1) living in an off- campus residence that is not conducive for learning, (2) participating in part-time paid employment, (3) the current structure of the curriculum, (4) inadequate academic and clinical support, and (5) unfavourable physical educational environment. Furthermore, the findings revealed that nursing students resort to: (1) a surface approach to learning and (2) active academic engagement. Based on these findings, it is evident that nursing students at the university understudy are overwhelmed with various challenges that pose a threat to their academic performance and success. Thus, there is a need for interventions to be put in place in response to the challenges experienced by the undergraduate nursing programme.